SEBASTIÃO UCHOA LEITE: O IMAGINÁRIO DO DUPLO NITERÓI - Rita, Ana Carolina Rocha Santa (2011)
The poetics of Sebastião Uchoa Leite has clear links with the negative categories, typical of modernity. These relationships allow it to be close to that part-ironic coloquial inaugurated by Tristan Corbiere and Jules Laforgue during the Symbolism and it is associated with the labels "antilírica" and / or antipoetics . This paper aims at pointing out and explaining these associations, besides addressing such relationships from the conditions in which the poetic subject is presented - deployed in itself double and horror characters - a bad choices to human form and favorable to the configuration of the monster. We also intend to study the relation of this poetry to the cinema, the record of citations of people, characters and other elements of the film universe, as well as the use of cinematic resources in the poetic work of the author. The inclusion of movie and monsters in the poems of Uchoa Leite problematizes the tradition of the lyric, legitimizes the originality of the poet and raises concerns about human identity and the dialogue between the arts, to be explored.